Single-center experience in vaccination of children in special risk groups: A multidisciplinary institutional consensus protocol - BARIŞ, HATİCE EZGİ; KEPENEKLİ KADAYİFCİ, EDA; ÜTÜK, BURAK; ŞAHİN, PINAR; TOKUÇ, AYŞE GÜLNUR; KOÇ, AHMET; AYDINER, ELİF; BORAN, PERRAN (My University, 2023)
Objective: Despite marked improvements in the accessibility of childhood vaccines, knowledge gaps remain about the vaccination of children in special risk groups (SRG). This study aimed to analyze the clinical data of children vaccinated in SRG in a single-center unit to contribute to the clinical evidence for the specific planning of immunization of children in SRG. The secondary aim is to present institutional consensus on the vaccination of children in SRG. Materials and Methods: This retrospective study was conducted at a single-center pediatric vaccination clinic. Patient charts between 2018 and 2021 were retrospectively reviewed, and clinical and laboratory data were extracted. Serial joint meetings with multiple healthcare pro-fessionals were performed to develop an institutional protocol for vaccination. Results: There were 479 children vaccinated between 2018 and 2021 for reasons such as post-chemotherapy, after hematopoietic stem cell transplantation, before/after solid organ trans-plantation, allergies, and chronic diseases. Of these, 298 (62.2%) children vaccinated in the unit due to a history of food or vaccine allergies were excluded. One hundred eighty-one children were vaccinated at a median age of 11 [7-15] years. Most children were vaccinated after treatment for malignancies. Solid tumors were the most frequent malignancy (67%), followed by acute lymphoblastic leukemia (29.0%) and acute myeloid leukemia (4.0%). Institutional vaccination protocols for cancer survivors, hematopoietic stem cells, and solid organ recipient children were developed and presented. Conclusion: There is a need to prepare national guidelines for vaccinating children with altered immunocompetence. Sharing vaccination practices by multidisciplinary vaccination units might increase and provide knowledge to develop national policies.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Health Sciences; Klinik Tıp (MED); Klinik Tıp; PEDİATRİ; Clinical Medicine (MED); CLINICAL MEDICINE; PEDIATRICS; Pediatri, Perinatoloji ve Çocuk Sağlığı; Pediatrics, Perinatology and Child Health; Cancer; children; hematopoietic stem cell transplantation; solid organ transplantation; vaccine; Cancer; children; hematopoietic stem cell transplantation; solid organ transplantation; vaccine